PENDIDIKAN DAN PEMBINAAN ROHANI ANAK: MODEL, STRATEGI, DAN PELUANG - Maria Purba; Roretta Hutabarat; Sartika Sihotang; Damayanti Nababan (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2022)
This writing is base on the problem of the pastor’s inability the church to implement an effective community development program. Moreover, if this judged based on implementation of the chuch’s vision and mision, many churches are not accurate incarrying out spiritual formation properly. Another problem is the lack of time the congregation participates in a coaching program implemented in the church will affect the congregation’s lack of knowledge and understanding of God’s word, this will affect the spiritual quality of the congregation. The research method used in this paper is a descriptive qualitative study of literature by examining various literatures relating to subject matter discussed. Through in-depth study and analysis, it is hoped that the pastors will provide concrete steps in planning and conducting effective coaching of church members. The result of this reseach to provide strategic steps and models of spiritual formation that are accurate and measurable and are able to increase the understanding of God’s word and make the spiritually mature as measured by changes in behaviour.